Al-Qaida in Afghanistan - Stenersen, Anne (Cambridge University Press, 2017)
Introduction -- Vanguards -- Training under pressure -- Return of the Sheikh -- The troublesome guest -- Training under the Taliban -- Taliban's policies towards the Arabs -- Frontline participation -- International terrorism -- Al-Qaida's dual strategy -- Epilogue